Réponses

Meilleure réponse !
2012-07-15T17:44:00+02:00

A  x+7=-2     x= -2 - 7 = - 9 

B   -5x = -2  donc  x = -2 / -5 = 2 / 5 

C   2x + 1 = - 4  donc   2x = -4 + 1  d'où   2x = - 3   alors  x = -3 / 2

D   4x - 3 = - 7   donc   4x = - 7 + 3 d'où  x= -4 / 4 = - 1 

E    4x = 2x + 3   donc 4x - 2x = 3  d'où  2x = 3 alors  x = 3 / 2 

F    7x - 2 = 5 - x  donc  7x + x = 5 + 2 d'où  8x = 7  alors  x = 7 / 8 

G    5 ( 8 + 2x ) = 2 ( 1 - x )  on développe   40 + 10x = 2 - 2x d'où  10x + 2x = 2 - 40

       donc   12x  = 38   alors x = 38 / 12  = 19 / 6 

H   5x + 6 - 3 ( 1 + 5x ) = 4x - 3  donc 

      5x + 6 - 3  - 15x = 4x - 3  alors

      -10x - 4 x + 3 = - 3  donc 

           - 14x   =  - 3 - 3 

               x =     -6 / 14  

               x =     -3 / 7